A Source Hiding Identity-Based Proxy Reencryption Scheme for Wireless Sensor Network. (17th October 2018) - Ge, Chunpeng; Xia, Jinyue; Wu, Aaron; Li, Hongwei; Wang, Yao
Abstract : Wireless sensor network (WSN), which extends the typical Internet environment to Internet of Things, has been deployed in various environments such as safety monitoring, intelligent transportation, and smart home. In a WSN, encryption is typically used to protect data that are stored in wireless devices. However some features like data sharing can be affected if the traditional encryption is used. A secure mechanism should support a gateway of the network to directly convert a user's encrypted data (encrypted pollution data) to a new user's encryption without exposing the underlying plaintext data during the whole sharing phase. In this work, a new source hiding identity-based proxy reencryption scheme (SHIB-PRE) is proposed to deal with the issue. The proposed SHIB-PRE scheme supports a proxy (gateway or cloud server) to transform a user's encrypted date to a new user's ciphertext as long as the proxy has the proxy reencryption key. In SHIB-PRE, the encrypted pollution data is kept secure from the proxy and the relationship between a source ciphertext and a reencrypted ciphertext is concealed from the outside eavesdropper. In this paper, we give an introduction to the definition of a source hiding identity-based proxy reencryption and its chosen plaintext security model. Further, a concrete construction will be presented and proven chosen plaintext secure under the q - D D H E assumption in the standard model.